Giant hepatic capillary hemangioma, a diagnostic dilemma: case report - Dhali, Arkadeep; Hazra, Anirban; Roger, B. Rathna; Dhali, Gopal Krishna; Sarkar, Avik (International Journal of Advances in Medicine, 2021)
Hepatic Hemangiomas (HH) are benign tumors of the liver consisting of a blood-filled cavity supplied by the hepatic artery. Most of the HH are asymptomatic and are discovered incidentally during radiological imaging of various unrelated pathology. Typical capillary hemangiomas range from a few millimeters to three centimeters and are unlikely to generate any future symptomatology. However, giant liver hemangiomas (more than 10 cm) are a very rare entity and might become symptomatic, hence requiring prompt intervention. We are reporting this case to make the readers aware of the pitfalls and radiological uncertainties while interpreting vascular lesions of the liver. We reported a case of a 21-year-old female with complaint of awareness of a mass over the right upper abdomen since a period of one year which has been gradually increasing in size. On pre-operative Contrast-Enhanced Computed Tomography, features suggestive of Fibrolamellar variant of Hepatocellular Carcinoma was found which was substantiated by biochemical investigations. However, post-operative histopathological examination revealed a capillary hemangioma.